KONTRIBUSI EKSPOR PRODUK TURUNAN KELAPA TERHADAP TOTAL EKSPOR DI PROVINSI SULAWESI UTARA - YUNITA . KUNTEL (Universitas Sam Ratulangi, 2012)
This research has a purpose to know the kind of exported coconut derivative product which exported as well as its contribution for the total of export in the North Sulawesi Province. Â This research conducted in three months, started from march until may, 2012. The data collected from the agency of trade and industries in North Sulawesi Province was the secondary data of the North Sulawesi total export during 2006 until 2011. Data analysed descriptively and pointed out in graphics and described. Â Resulf of the research shows that the coconut derivate product has an important contribution for the total export of North Sulawesi Province. In 2011, 53,37 percent of export in the North Sulawesi dominated by coconut derivative product. The largest contribution of coconut derivative product is coconut oil where more than 46,67 percent of the total export from North Sulawesi. The average contribution of coconut derivative product from 2006 until 2011 about 51,86 percent of the North Sulawesi Province total export. From coconut derivative product contribution, coconut oil has a largest contribution which is 46,09 percent, followed by the contribution 2,41 percent ofÂ copra residue; 1,98 percent of coconut powder; 1,01 percent of copra; 0,20 percent of active carbon and 0,17 percent of cranium charcoal.